Pengaruh Kompetensi Dan Motivasi Kerja Terhadap Kinerja Dengan Kepuasan Kerja Karyawan Sebagai Variabel Intervening Pada Encar Daihatsu Palembang - Desy Afriliani; Manisah; Sari Sakarina (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
This study aims to determine the Influence of Competence and Work Motivation on Performance with Employee Job Satisfaction as an Intervening Variable at Encar Daihatsu Palembang. The population of this study was 43 people. Data analysis used in this study is the Structural Equation Model (SEM) analysis method operated through the Partial Least Square (PLS) program. The results of the study indicate that there is an Influence of Competence and Work Motivation on Performance with Employee Job Satisfaction as an Intervening Variable at Encar Daihatsu Palembang with the equation Y = 0.753x_1 + 0.468x_2 + ε_1 and the equation Z = 0.156x_1 + 0.260x_2 + 0.144Y + ε_2 there is an influence of competence on job satisfaction indicated by the equation of p-values ​​of 0.000 <0.05 and t-statistics of 4.973> 1.960, competence has a significant effect on performance indicated by p-values ​​of 0.060> 0.05 and t-statistics of 1.884 <1.960, Motivation has an effect on Employee Performance indicated by p-values ​​of 0.053> 0.05 and t-statistics of 1.941 <1.960, 1.960, job satisfaction has an effect on Employee Performance indicated by p-values ​​of 0.000 <0.05 and t-statistics of 6.264> 1.960. The R2 value for the latent variable Job Satisfaction as a mediating variable is 0.177, which means that the value identifies that the variation in Employee Job Satisfaction can be explained by exogenous latent variables (Competence and Motivation) of 17.7% while the remaining 82.3% is explained by other variables and the R2 value for the latent variable performance is 0.218, which means that the value identifies that the variation in performance can be explained by exogenous variables of 21.8% while the remaining 78.2% is explained by variables not included in the study. From the model built in this study, and from the results of the hypothesis test using Smart-PLS, it can be suggested that every employee and assisted by the company should always improve their competence so that their ability to complete work can be further improved. Improving employee job satisfaction should be a concern for the company, because it will affect the level of performance produced. Good work motivation should always be possessed by employees so that they can be a driver to achieve the best results